Implementasi CSR PT PBS Terhadap Lingkungan Sosial Ekonomi di Gampong Glee Siblah - Rindi Ani; Ida Zufina; Fitri Derminta Berutu; Sopar (Indo Publishing, 2025)
PT PBS (Potensi Bumi Sakti) is located in Glee Siblah Village, where the majority of the population relies on rubber plantations for their livelihood. This study aims to analyze the implementation of PT PBS's CSR programs on the social environment in Glee Siblah Village. The research method used a descriptive qualitative approach, with data collected through interviews and observations. The results indicate that PT PBS makes a positive contribution to the community's economy, but also has a negative impact on the environment. Existing CSR programs are still limited and not yet optimal, necessitating evaluation and improvement to provide greater benefits to the community.